The Give-and-Take Interaction Between the Tumor Microenvironment and Immune Cells Regulating Tumor Progression and Repression - Pernot, Simon; Evrard, Serge; Khatib, Abdel-Majid (Frontiers in Immunology, 2022)
A fundamental concern of the majority of cancer scientists is related to the identification of mechanisms involved in the evolution of neoplastic cells at the cellular and molecular level and how these processes are able to control cancer cells appearance and death. In addition to the genome contribution, such mechanisms involve reciprocal interactions between tumor cells and stromal cells within the tumor microenvironment (TME). Indeed, tumor cells survival and growth rely on dynamic properties controlling pro and anti-tumorigenic processes. The anti-tumorigenic function of the TME is mainly regulated by immune cells such as dendritic cells, natural killer cells, cytotoxic T cells and macrophages and normal fibroblasts. The pro-tumorigenic function is also mediated by other immune cells such as myeloid-derived suppressor cells, M2-tumor-associated macrophages (TAMs) and regulatory T (Treg) cells, as well as carcinoma-associated fibroblasts (CAFs), adipocytes (CAA) and endothelial cells. Several of these cells can show both, pro- and antitumorigenic activity. Here we highlight the importance of the reciprocal interactions between tumor cells and stromal cells in the self-centered behavior of cancer cells and how these complex cellular interactions control tumor progression and repression.